(untitled) (Interfaces: A Journal of Medieval European Literatures, 2024)
In 1638 the Vatican Typography printed a book in memory of Nicolas-Claude Fabri de Peiresc; the book was dedicated to Cardinal Francesco Barberini and it is a clear example of the way in which political (and ecclesiastical) power influenced the cultural dynamics of the seventeenth century. Among the scholars who composed verses for the death of de Peiresc we find Francesco Arcudi, a literate priest from the Greek-speaking area of Southern Apulia, who migrated to Rome to study in the Greek College of St. Athanasius. He showed his Greek (linguistic and liturgical) knowledge at the court of Francesco Barberini. Arcudi’s poetic production is, in its greatest part, dedicated to Pope Urban VIII Barberini and his nephew, Cardinal Francesco; the poems are written for various occasions, aiming to celebrate the power and glory of the pope’s and cardinal’s family. Of great interest are Arcudi’s τεχνοπαίγνια, figure epigrams inscribed in the shape of a bee (the arms of the Barberini family) or an eagle (symbol of Barberini’s power), here edited for the first time. After an overview of Francesco Arcudi’s personality and poetic production, the paper aims to advance our understanding of the cultural landscape (during the pontificate of Pope Barberini) and show the way in which Barberini’s patronage influenced Arcudi’s work and that of other scholars in the first half of the seventeenth century.